Improved anchoring nails: design and analysis of resistance ability - Z. H. Zhou; X. Z. Chen; X. W. Chen; Y. X. Wang; S. Y. Zhang; S. F. Sun; J. Z. Zhen (BMC, 2018)
Abstract Background Anchorage is one of the most important treatments for severe temporomandibular joint disorder (TMD). Anchoring nails have shown great success in clinical trials; however, they can break under pressure and are difficult to remove. In this study, we aimed to evaluate an improved anchoring nail and its mechanical stability. Methods The experiment consisted of two parts: a tensile test and finite element analysis (FEA). First, traditional and improved anchoring nails were implanted into the condylar cortical bone and their tensile strength was measured using a tension meter. Second, a three-dimensional finite element model of the condyles with implants was established and FEA was performed with forces from three different directions. Results The FEA results showed that the total force of the traditional and improved anchoring nails is 48.2 N and 200 N, respectively. The mean (±s.d.) maximum tensile strength of the traditional anchoring nail with a 3-0 suture was 27.53 ± 5.47 N. For the improved anchoring nail with a 3-0 suture it was 25.89 ± 2.64 N and with a 2-0 suture it was above 50 N. The tensile strengths of the traditional and improved anchoring nails with a 3-0 suture was significantly different (P = 0.033-< 0.05). Furthermore, the difference between the traditional anchoring nail with a 3-0 suture and the improved anchoring nail with a 2-0 suture was also significantly different (P = 0.000-< 0.01). Conclusion The improved anchoring nail, especially when combined with a 2-0 suture, showed better resistance ability compared with the traditional anchoring nail.